Attractiveness bias: A cognitive explanation. (2017) - Schein, Stevie S.; Trujillo, Logan T.; Langlois, Judith H.
Abstract: According to cognitive averaging theory, preferences for attractive faces result from their similarity to facial prototypes, the categorical central tendencies of a population of faces. Prototypical faces are processed more fluently, resulting in increased positive affect in the viewer.